Peningkatan Kualitas Pembelajaran Melalui Lesson Study Berorientasi Pada Pengembangan Kompetensi Guru - Aliyil Mahsum; Cici Wiladia; Moh Syaifur Rohman; Mas odi Mas odi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Improving the quality of learning is a major challenge in the world of education that demands innovation and continuous development of teacher competencies. Lesson study, as a collaborative approach, offers a solution by strengthening teacher competencies in designing, implementing, and evaluating learning. This study uses a library method by analyzing various literature related to the application of lesson study in various educational contexts which are then collected and analyzed. The results of the study indicate that lesson study has a positive impact on improving the quality of learning through collaborative and reflection-based learning. Teachers involved in this process become more adaptive to student needs, enrich learning strategies, and are able to identify learning obstacles directly. The conclusion of this study confirms that lesson study not only improves teacher competency, but also contributes significantly to the overall quality of education, especially in creating more effective and student-centered learning.